2014
DOI: 10.1111/iep.12110
|View full text |Cite
|
Sign up to set email alerts
|

Spleen tyrosine kinase contributes to acute renal allograft rejection in the rat

Abstract: Kidney allografts induce strong T-cell and antibody responses which mediate acute rejection. Spleen tyrosine kinase (Syk) is expressed by most leucocytes, except mature T cells, and is involved in intracellular signalling following activation of the Fcγ-receptor, B-cell receptor and some integrins. A role for Syk signalling has been established in antibody-dependent native kidney disease, but little is known of Syk in acute renal allograft rejection. Sprague-Dawley rats underwent bilateral nephrectomy and rece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…In another experimental model of renal allograft rejection, where Sprague-Dawley rats underwent bilateral nephrectomy and orthotopic renal transplant from Wistar rats, Ramessur Chandran et al [37] showed dense leukocytic infiltration with strong Syk expression in the allograft. Administration of Syk inhibitor (CC0482417) significantly improved allograft function, reduced leukocytic infiltration and attenuated acute tubular injury and peritubular capillary thrombosis [37]. …”
Section: Pathogenic Role Of Syk In Renal Disease (Table 1)mentioning
confidence: 99%
“…In another experimental model of renal allograft rejection, where Sprague-Dawley rats underwent bilateral nephrectomy and orthotopic renal transplant from Wistar rats, Ramessur Chandran et al [37] showed dense leukocytic infiltration with strong Syk expression in the allograft. Administration of Syk inhibitor (CC0482417) significantly improved allograft function, reduced leukocytic infiltration and attenuated acute tubular injury and peritubular capillary thrombosis [37]. …”
Section: Pathogenic Role Of Syk In Renal Disease (Table 1)mentioning
confidence: 99%